Perempuan dan Perkebunan Sawit - Puspitasari, Astrid (Universitas Jambi, 2023)
Nowadays Indonesia is the largest palm oil producer in the world. Oil palm plantations provide a large contribution to foreign exchange for Indonesia. This sector is so vital that it is often referred to as green gold. The development of palm oil in Indonesia is also accelerating and expanding to nearly all regions in Indonesia. However, behind the aggressive development of oil palm plantations in Indonesia, there is another aspect that deserves attention, and that is the fate of the vulnerable group of women. Women are greatly and significantly affected by the existence of oil palm plantations, particularly for women who become laborers in oil palm plantations as a result of the loss of their land. Working conditions and poor pay make the conditions for oil palm workers far from prosperous, especially because the majority of women workers are casual daily workers without work contracts and defined rights, so they can vulnerable to be terminated. Additionally, women and children often have to help their husbands and fathers who work as laborers to meet unrealistic targets to avoid punishments or wage cuts. Given this, it is crucial for the Government of Indonesia to issue a particular protection policy for oil palm plantation laborers in order to safeguards their rights.